Congenital Pseudoarthrosis of Clavicle: A Case Report and Review of Literature - Alharthi, Abdulaziz Saleh; Alsayed, Mokhtar Ahmed (International Journal of Innovative Research in Medical Science, 2022)
Congenital pseudarthrosis of the clavicle (CPC) is considered one of the rare conditions that regularly diagnosed during the first years if life and resulted from the failure of the union process of the ossification nuclei of the clavicle. Surgical management is considered the first line treatment of this condition however, associated with some complications. In this case study, we reported a case of 2- year- old- boy presented with Congenital pseudarthrosis of the clavicle that was treated with conservative management.